Aktifitas Rebranding PR dalam Perusahaan Elite Marketer untuk Membangun Brand Awareness. - Ria Nadira Pratiwi (2020)
The research was conducted because it wanted to see whether the rebranding activities carried out by the public relations company ELITE MARKETER could build the expected brand awareness or not. How the public and consumers of ELITE MARKETER know about the change of name and business changes made by Digital Marketer Indonesia (DMID) to Elite Marketer (EM). The purpose of this study is to find out how EM conducts rebranding activities in creating brand awareness and whether it is optimal in the process. Data collection techniques used were in-depth interviews (in-depth interviews) and direct observation to the EM office. The results showed the company's rebranding was not in accordance with the expectations of key informants. The conclusion obtained is that rebranding activities are hampered by financial problems and the advice I can give is the need for more mature planning.